Immigration Information Counseling in the context of realizing a form of direct literacy for school children - Rita Kusuma; Olyvia Sindiawaty (Jurnal Abdimas Imigrasi, 2020)
One of the immigration functions that is listed in Law No. 6 of 2011 is one form of immigration services. Immigration services can be in the form of services at the Technical Implementation Unit (UPT) such as at the immigration office, as well as by providing information on matters that are carried out in the immigration field, for example by providing a form of literacy in the form of counseling to the community around the work unit and others. Information dissemination activities in the form of outreach, one of which is a form of information dissemination activities that can be carried out in order to realize the values ​​of the immigration function, as stipulated in Law No. 6 of 2011. This is one of the important assessments for the Immigration Office organizing, and immigration itself. With counseling to people who are still laymen and do not understand anything at all about immigration, as one part of the State Civil Apparatus, it is better to educate the life of the nation as a form of the embodiment of the values ​​of Pancasila. Especially for people who are still in education. Such as High School and Vocational High School. As the seeds of the successor of the nation, it is time for them to understand what the function of immigration is in the hope that in the future if there is something suspicious happening around their neighborhood involving Foreign Citizens, they understand which party to report the form of the crime and can disseminate information if you are interested in doing an overseas scholarship in order to continue their studies.